2006
DOI: 10.1016/j.cell.2006.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Reactive Oxygen Species and Neurodegeneration by the PGC-1 Transcriptional Coactivators

Abstract: PPARgamma coactivator 1alpha (PGC-1alpha) is a potent stimulator of mitochondrial biogenesis and respiration. Since the mitochondrial electron transport chain is the main producer of reactive oxygen species (ROS) in most cells, we examined the effect of PGC-1alpha on the metabolism of ROS. PGC-1alpha is coinduced with several key ROS-detoxifying enzymes upon treatment of cells with an oxidative stressor; studies with RNAi or null cells indicate that PGC-1alpha is required for the induction of many ROS-detoxify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

112
1,697
5
19

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 1,993 publications
(1,833 citation statements)
references
References 42 publications
112
1,697
5
19
Order By: Relevance
“…38 Previous studies have shown that PGC-1R regulates fundamental metabolic pathways, including fatty acid oxidation, 39 mitochondrial oxidative phosphorylation, 40 gluconeogenesis, 41 and ROS metabolism. 42 For example, PGC-1R is activated to promote expression of genes involved in gluconeogenesis and fatty acid oxidation in hepatocytes upon fasting. 41,43 Similarly, forced expression of PGC-1R in muscle robustly enhances mitochondrial biogenesis, coupled to a shunt of energy dependence on fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…38 Previous studies have shown that PGC-1R regulates fundamental metabolic pathways, including fatty acid oxidation, 39 mitochondrial oxidative phosphorylation, 40 gluconeogenesis, 41 and ROS metabolism. 42 For example, PGC-1R is activated to promote expression of genes involved in gluconeogenesis and fatty acid oxidation in hepatocytes upon fasting. 41,43 Similarly, forced expression of PGC-1R in muscle robustly enhances mitochondrial biogenesis, coupled to a shunt of energy dependence on fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Since the increase of mitochondrial number/activity induced by PGC-1␣ may cause in principle an increase of ROS production, then the protein plays a role in the regulation of the ROS metabolic program, leading to over-expression of ROS detoxifying enzymes, in particular MnSOD (St-Pierre et al, 2006). ROS level in the matrix, where superoxide is mostly released, is thus maintained definitely low to have cells functioning normally.…”
Section: Resultsmentioning
confidence: 99%
“…173,175 This might be the reason for the strong expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha in PV þ interneurons, at least during certain stages of brain development. 176,177 Peroxisome proliferatoractivated receptor gamma coactivator 1-alpha has the capability to induce the expression of enzymes involved in glutathione biosynthesis as well as of ROS-detoxifying enzymes such as As a perspective, the functional consequences of metabolic stress in fast-spiking interneurons are illustrated. Even moderate metabolic stress, which occurs either acutely (e.g., hypoxia/ischemia and mitochondrial poisoning) or chronically (e.g., arteriosclerosis or mitochondrial disorders), might cause dramatic decreases in ATP levels and GABA release in fast-spiking interneurons (switch from intermittent to solid blue spheres).…”
Section: Perspective: Metabolic and Oxidative Stress In Fast-spiking mentioning
confidence: 99%